Analisa Kualitas Website SMK Negeri 1 Mandor Terhadap Kepuasan Pengguna Dengan Metode Webqual 4.0 - Filipus Nanda Kurniawan; Eva Zuraidah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Foreman 1 State Vocational High School currently has a website with the site address https://smkn1mandor.sch.id/ as a means of delivering academic information needed by users. However, so far there are still obstacles in the field, namely that there are still many students who cannot access the website properly because the academic consultation feature cannot be accessed optimally, there is a lot of content that is not updated, students lack enthusiasm for using website profile and basic information such as the school's complete profile has not been included in its entirety on the website. For this reason, researchers conducted an analysis of student satisfaction as users of website services using the webqual 4.0 method which focuses on 3 webqual 4.0, namely Usability Quality, Information Quality, and Interaction Service Quality. This study used a statement instrument based on the webqual 4.0, using a questionnaire distributed to 87 respondents taken based on simple random sampling from a population of 450 active students. Data processing used SPSS version 26. Based on the test results and data analysis in this study, it can be concluded that the four webqual 4.0 variables, namely Usability Quality, Information Quality, and Service Interaction Quality on the website are in a reasonably high category with satisfaction scores in the satisfied category. The results of the evaluation in this study provide input for school's service interactions website.